Health Profile of Etawah Crossbreds Given Probiotics at Smallholder Farms in Kampung Bugis, Desa Serangan, Bali - M. M., Bambar; Doloksaribu, L.; Putra, I G. A. A. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
The purpose of this study was to identify the common types of disease, particularly endoparasitic infection that affected the health profile of goats rearing in Kampung Bugis, Serangan Village, Bali.  Data was collected through direct observations, structured formal household interviews, and key informant interviews that were conducted from July to September 2018.  Each of the two farmers housed their goats in group housing system and fed forage of approximately 10% of body weights of goat/head/day, but only one goat farmer added a mixture of probiotic with drinking water ad libitum .  Parameters observed were faecesand FAMACHA © scores.  FAMACHA © score of goats in Control group 1.00 ± 0.00 was significantly lower than those of goats in Treatment group 1.11 ± 0.04 (P<0.05), however, both groups were indentified as heathly and not suffering from anaemia.  Haemonchus contortus sp., Ostertagia sp., and Fasciola sp ., were types of worm found in the digestive tract of goats reared in Serangan Village, Bali.  Results of this study showed that the worm infestation rate was of mild infection i.e. 37.5% and 33.3% for non probiotic and probiotic treatment.To sum up, providing a mixture of probiotic with drinking water ad lib tended to reduce the endoparasitic infection in goats reared in Serangan Village.   Keywords : Health profile, infection, endoparasites , probiotics